(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Rural economic development, especially through the establishment of the Central Kesiut Traditional Village LPD in Bali, plays a key role in improving the welfare of village communities, but it is necessary to increase community trust to create loyalty to the LPD. Thiss ressearch aimss to determines thes effects ofs service quallity on customer trust in the Kesiut Tengah Traditional Village Credit Institution, Tabanan. to determines the influences of customer trust on customer loyallty at thes Kesiut Tengah Traditional Village Credit Institution, Tabanan. To determines the influence of service qualiity on customer loyallty at the Central Kesiut Traditional Village Credit Institution, Tabanan. To determines the roles ofs customers trust in mediatiing services quality on customer loyaltys at the Kesiut Tengah Traditional Villages Credit Institution, Tabanan. Thes sample populations for this research was the LPD customers of the Central Kesiut Traditional Village, totaling 88 peoplle who were determined using the Slovins formula ands testeds usings path anallysis techniques. The resullts of thiss research show thats service quallity has a signifficant effects on customer trust and loyalty at the Kesiut Tengah Traditional Village Credit Institution, Tabanan, with customer trust acting as a mediator in the rellationship bettween servicea quallity and customer loyallty